Text Mining Application of Computational Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
One of the foremost requirements of modern man is undoubtedly the possibility to access the desired information with minimal effort. And it is an undeniable fact that the amount of storing information digitally is increasing minute by minute.As people are moving to a digital world of information or knowledge. Whenever one wishes to collect some information, the first task is to identify the relevant points from the vastness of digitally stored data. The upsurge and flourishing of Text Mining paved the way for a new beginning in the area of Information Extraction (IE) and Information Retrieval (IR). As the term suggests, it is to mine relevant information from the text document. The text document could be un-structured or semistructured. There exist different approaches and methods for text mining and most of these techniques are computational linguistics . The entitled paper attempts to provide a deliberation on the existing various concepts, techniques, pre-processing steps, applications and issues of text mining.